High-quality lap welding method for dissimilar materials based on laser surface treatment
Through laser surface treatment and friction stir lap welding technology, the connection problem of metal and fiber reinforced composite materials is solved, high-quality welding of different types of materials is achieved, connecting strength and fatigue performance are improved, and cost and environmental impact are reduced.
Patent Information
- Application Number
- CN202411287715.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
It is difficult for the prior art to achieve high-quality connection between metal and fiber-reinforced composite materials, and traditional surface treatment methods have problems such as environmental pollution, high cost and low production efficiency.
Adopt high-quality overlap welding method of heterogeneous materials based on laser surface treatment. By etching the target microstructure on the surface of metal sheets and introducing Schiff alkali polymer, combined with friction stir overlap welding technology, the connection area and strength are improved and the welding is reduced. stress.
It significantly improves the connection strength and fatigue performance between different materials, reduces costs, simplifies the process flow, improves processing efficiency, and reduces the temperature and hole defects in the welding area.
Smart Images

Figure CN119140997A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal and fiber reinforced plastic dissimilar material connection, and in particular to a high-quality lap welding method for dissimilar materials based on laser surface treatment. Background Art
[0002] In pursuit of the vision of energy conservation, emission reduction and environmental protection, in recent years, lightweight structural design has been gradually considered in many fields such as automobiles, aerospace and medical equipment. Lightweight metal materials (magnesium alloys, aluminum alloys, titanium alloys, etc.) have the characteristics of light weight, low density, high strength and strong weldability. Fiber (especially carbon fiber) reinforced composite materials have the characteristics of light weight, high specific strength, good corrosion resistance and excellent fatigue resistance, so they are widely used in the above fields.
[0003] The two materials each have their own advantages. Welding them together can not only meet the requirements of lightweight design, but also combine the excellent properties of the two materials to obtain a high-quality structure. However, due to the huge differences in mechanical properties, physical properties and chemical properties, direct welding cannot be achieved. The main problem is that it is difficult for the two materials to produce atomic or molecular bonding, so it can only be achieved indirectly. One of the mainstream methods is to treat the surface of the material before welding to remove oil and impurities on the surface, provide new connection sites, and achieve close contact between the two materials.
[0004] At present, the surface treatment methods that have been studied or applied to metals and fiber-reinforced composites mainly include mechanical treatment (laser etching, sanding, shot peening, etc.) and chemical treatment (chemical etching, anodizing, etc.). The former has the effect of increasing the connection area and forming a mechanical interlocking structure, and the latter can introduce new chemical bonds. However, chemical treatment will produce a large amount of wastewater, waste gas, and waste, which not only pollutes the environment but also increases costs. Most mechanical treatments will increase material loss, and the dust and fine particles generated during the process will also pollute the environment. In addition, the noise problem caused by equipment vibration cannot be ignored. Compared with these methods, laser surface treatment technology has the advantages of environmental friendliness, low time cost, high dimensional accuracy, and strong stability. It has been used to etch different microstructures on the surface of materials and enhance the strength of welded joints.
[0005] In the context of current technological development, patent CN113414496A proposes a method for enhancing the connection strength between composite materials and metals by ultrafast laser processing, aiming to significantly enhance the connection strength between fiber-reinforced composite materials and metals by removing the oxide film on the metal surface and accurately etching the microstructure. This method strengthens the mechanical anchoring effect of heterogeneous structural joints by expanding the actual contact area, thereby achieving a significant improvement in shear strength. However, although the introduction of microstructures effectively improves the connection performance, it is also accompanied by the problem of stress concentration, which limits the upper limit of strength improvement to a certain extent. Patent CN114571736A discloses a method for ultrasonically enhanced connection of metal / chopped carbon fiber composite materials, which constructs microstructures on the surface of the material and introduces chemically active sites through electrolytic processing combined with silane coupling agent treatment, and then uses ultrasonic welding technology to effectively promote the bonding between dissimilar materials. Although this method shows advantages in connection effect, its complex chemical treatment process reduces the overall production efficiency. Therefore, it is urgent to provide a high-quality lap welding method for metal and fiber-reinforced composite plates based on laser surface treatment. Summary of the invention
[0006] Purpose of the Invention In order to solve the current connection problem of metal and fiber reinforced composite materials, the present invention provides a high-quality lap welding method for dissimilar materials based on laser surface treatment. The obtained microstructure is more compact in arrangement, which improves the utilization rate of the area to be welded and further increases the connection area between dissimilar materials. Secondly, the microstructure is more layered in space, which can effectively reduce the welding internal stress in the area to be welded and make the stress distribution more uniform, greatly improving the strength and fatigue performance of the welded joint.
[0007] To achieve the above object, the present invention provides the following technical solutions: A high-quality lap welding method for dissimilar materials based on laser surface treatment comprises the following steps: S1: Laser surface treatment of metal sheets, etching of target microstructures in the area to be welded, and introduction of Schiff base polymers containing Schiff bases -RC=N- and carbonyl groups -C=O; S2: Stir friction lap welding the treated metal sheet and the untreated fiber reinforced composite sheet.
[0008] As a further description of the above scheme, in step S2, the metal plate is made of magnesium alloy, aluminum alloy or titanium alloy; the fiber reinforced composite plate is a carbon fiber reinforced thermoplastic resin plate; the thermoplastic resin can be selected from PEEK, PA66 or PPS; the thickness of the metal plate and the fiber reinforced composite plate are both 1.5-3mm.
[0009] As a further description of the above scheme, in step S1, the central wavelength of the laser surface treatment of the metal plate is 1064nm; the pulse width of the laser surface treatment is 9-30ns; the laser frequency of the laser surface treatment is 450-600kHz; the laser power of the laser surface treatment is 15-25W; the scanning speed of the laser surface treatment is 10-30mm / s, and the number of scans is 3-5 times.
[0010] As a further description of the above scheme, in step S1, the metal sheet is laser surface treated twice. The first laser surface treatment is performed in the area to be welded to etch out the target microstructure, and then terephthalaldehyde C8H6O2 and aniline C6H5NH2 are introduced into the area to be welded (3). The second laser surface treatment is performed to heat the terephthalaldehyde C8H6O2 and aniline C6H5NH2 introduced into the area to be welded (3) to generate a Schiff base polymer, which then reacts and bonds with the metal ions of the metal sheet. As a further description of the above scheme, the cross-section of the target microstructure etched from the metal plate is a triangle, the three sides of the triangle are provided with concave arcs, and the corners of the triangle are rounded transition; a groove is formed between the etched target microstructure and the metal plate, the groove cross-section is an inverted trapezoid, the groove width is 200-400μm, the groove depth is 200-400μm, and the groove aspect ratio is 1-2.
[0011] As a further description of the above solution, in step S1, the width of the area to be welded is 10-12 mm.
[0012] As a further description of the above scheme, in step S2, the stirring head of the stir friction lap welding is perpendicular to the top of the area to be welded, and a lap method of metal plate on top and fiber reinforced composite plate on the bottom is adopted, and the lap width is 12-15mm.
[0013] As a further description of the above scheme, in step S2, the stirring head rotation speed of the friction stir lap welding is 1000-1500 r / min, the welding speed of the friction stir lap welding is 150-300 mm / min, and the sinking depth of the stirring head of the friction stir lap welding is 0.2-0.4 mm.
[0014] As a further description of the above scheme, in step S2, the metal sheet after laser surface treatment is sealed and stored before welding, and the surface of the fiber reinforced composite sheet is cleaned with a detergent and a soft cloth before welding to remove oil, dust and impurities.
[0015] The beneficial effects of the present invention include the following: 1. Compared with the traditional microstructure morphology (line, dot, grid, etc.), the microstructure of the present invention is more compact in arrangement, which improves the utilization rate of the area to be welded and further increases the connection area between dissimilar materials. Secondly, the microstructure is more layered in space, which can effectively reduce the welding internal stress in the area to be welded and make the stress distribution more uniform, greatly improving the strength and fatigue performance of the welded joint.
[0016] 2. After using the laser surface treatment process to etch a microstructure on the surface of the metal plate, the process is directly used to introduce the Schiff base polymer into the area to be welded. The spatial hierarchy of the microstructure makes the Schiff base polymer also have the characteristics of spatial distribution, providing a large number of reaction sites for metals and fiber-reinforced composites. While improving the mechanical properties of the joint, it also omits the tedious chemical treatment steps and improves the processing efficiency.
[0017] 3. Compared with the use of adhesive bonding, mechanical connection and other methods to connect metal and fiber reinforced composite materials, the welding process can further reduce costs, and there is no need to consider problems such as adhesive aging and weight gain of mechanical fasteners. In addition, stir friction lap welding, as a solid phase welding method, can effectively reduce the temperature of the connection area compared to the melting welding method, and can control the plastic deformation and flow of fiber reinforced composite materials.
[0018] 4. Under the coordinated control of laser surface treatment parameters and stir friction lap welding parameters, by finely adjusting the laser power, scanning speed, stirring head rotation speed, welding speed and other key parameters of stir friction lap welding, the fiber reinforced composite material can be completely filled with grooves. This synergistic effect not only effectively reduces the hole defects in the joint, but also significantly improves the overall load-bearing capacity and structural integrity of the joint.
[0019] 5. Since the process parameters of laser surface treatment and the geometric parameters of the microstructure (scanning spacing, geometric dimensions, etc.) can be flexibly adjusted, they are not limited to the test materials and welding methods listed in the present invention and have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of the microstructure morphology of the laser surface treatment of the present invention; Figure 2 From left to right, Figure a is the first scanning path diagram, Figure b is the second scanning path diagram, and Figure c is a schematic diagram of the structure obtained by etching.
[0021] Metal sheet; 2-Laser beam; 3-Area to be welded; 4-Target microstructure. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. On the contrary, the present invention covers any substitutions, modifications, equivalent methods and schemes made on the essence and scope of the present invention as defined by the claims. Further, in order to enable the public to have a better understanding of the present invention, some specific details are described in detail in the detailed description of the present invention below, and those skilled in the art can fully understand the present invention without the description of these details.
[0023] In this embodiment, the equipment used for laser surface treatment is a fiber nanosecond pulse laser system (SP-050P-AEP-ZFY, SPI laser), which can accurately control the morphology of the microstructure by adjusting parameters such as pulse width, laser frequency, laser power, scanning speed and scanning times. The welding device is a stir friction lap welder (HT-JM16X8 / 1), and the parameters such as the stirring head speed, stirring head travel speed, stirring head sinking depth and stirring head residence time can be set before welding. The stirring head automatically completes the welding process according to the program preset by the walking device.
[0024] A high-quality lap welding method for metal and fiber-reinforced composite plates based on laser surface treatment comprises the following steps: S1: laser surface treatment is performed on a metal sheet 1 by a laser beam 2, a target microstructure 4 is etched in a welding area 2, and a Schiff base polymer is introduced, wherein the polymer contains a Schiff base (-RC=N-) and a carbonyl group (-C=O); S2: Stir friction lap welding the treated metal sheet 1 and the untreated fiber reinforced composite sheet. The advantage of this method is that the fiber reinforced composite material undergoes plastic deformation during welding, and while flowing into the microstructure, it can react and bond with new polar functional groups, and a stronger mechanical interlocking structure is formed after the joint is cooled. In addition, compared with the traditional microstructure morphology, this structure can further reduce the welding internal stress in the area to be welded, and the distribution is more uniform, which effectively improves the strength and fatigue performance of the welded joint.
[0025] In step S2 of the present invention, the metal plate 1 is made of lightweight metal material, the metal plate 1 is made of magnesium alloy, aluminum alloy or titanium alloy, the fiber reinforced composite plate is a carbon fiber reinforced thermoplastic resin plate, the thermoplastic resin can be selected from PEEK, PA66, PPS, etc., wherein the thickness of the metal plate 1 and the fiber reinforced composite plate are both 1.5-3 mm.
[0026] In step S1 of the present invention, the metal plate 1 is surface treated with laser with a central wavelength of 1064 nm; a pulse width of 9-30 ns; a laser frequency of 450-600 kHz; a laser power of 15-25 W; a scanning speed of 10-30 mm / s and a scanning number of 3-5 times, in order to flexibly control the depth-to-width ratio of the target groove and ensure the stability of the etching effect.
[0027] This design uses a laser surface treatment process to etch a microstructure on the surface of the metal sheet, and then directly uses the process to introduce a Schiff base polymer into the area to be welded. The spatial hierarchy of the microstructure makes the Schiff base polymer also have the characteristics of spatial distribution, providing a large number of reaction sites for metals and fiber-reinforced composites. While improving the mechanical properties of the joints, it also omits the tedious chemical treatment steps and improves the processing efficiency. At the same time, compared with the use of adhesive bonding, mechanical connection and other methods to connect metals and fiber-reinforced composites, the welding process can further reduce costs, and there is no need to consider problems such as adhesive aging and weight gain of mechanical fasteners. In addition, stir friction lap welding, as a solid-phase welding method, can effectively reduce the temperature of the connection area compared to the melting welding method, and can control the plastic deformation and flow of fiber-reinforced composites.
[0028] In step S1 of the present invention, the metal sheet 1 is subjected to laser surface treatment twice. The first laser surface treatment is performed in the area to be welded 3 to etch out the target microstructure 4, and then terephthalaldehyde C8H6O2 and aniline C6H5NH2 are introduced into the area to be welded (3). The second laser surface treatment heats the terephthalaldehyde C8H6O2 and aniline C6H5NH2 introduced into the area to be welded (3) to generate a Schiff base polymer, which then reacts and bonds with the metal ions of the metal sheet 1.
[0029] The cross-section of the target microstructure 4 etched from the metal plate 1 of the present invention is a triangle, wherein the three sides of the triangle are provided with concave arcs, and the corners of the triangle are rounded transition; a groove is formed between the etched target microstructure 4 and the metal plate 1, the groove cross-section is an inverted trapezoid, the groove width is 200-400μm, the groove depth is 200-400μm, and the groove aspect ratio is 1-2.
[0030] Compared with the traditional microstructure morphology (line, dot, grid, etc.), the microstructure designed in this application is more compact in arrangement, which improves the utilization rate of the area to be welded and further increases the connection area between dissimilar materials. Secondly, the microstructure is more layered in space, which can effectively reduce the welding internal stress in the area to be welded and make the stress distribution more uniform, greatly improving the strength and fatigue performance of the welded joint. In addition, since the process parameters of the laser surface treatment and the geometric parameters of the microstructure (scanning spacing, geometric dimensions, etc.) can be flexibly adjusted, it is not limited to the test materials and welding methods listed in the present invention, and has broad application prospects.
[0031] In step S1 of the present invention, the width of the area 3 to be welded is 10-12 mm.
[0032] In step S2 of the present invention, the stirring head of the friction stir lap welding is perpendicular to the top of the area to be welded 3, and a lap method is adopted in which the metal plate 1 is on the top and the fiber reinforced composite plate is on the bottom, and the lap width is 12-15 mm.
[0033] In step S2 of the present invention, the stirring head rotation speed of the friction stir lap welding is 1000-1500 r / min, the welding speed of the friction stir lap welding is 150-300mm / min, and the sinking depth of the stirring head of the friction stir lap welding is 0.2-0.4 mm. Under the coordinated control of the laser surface treatment parameters and the friction stir lap welding parameters, the laser power, scanning speed of the laser, and the stirring head rotation speed and welding speed of the friction stir lap welding are finely adjusted to achieve plastic deformation and flow of the fiber reinforced composite material, and the groove is completely filled after cooling to obtain good weld formation. This synergistic effect not only effectively reduces the hole defects in the joint, but also significantly improves the overall load-bearing capacity and structural integrity of the joint.
[0034] In step S2 of the present invention, the metal plate 1 after laser surface treatment is sealed and stored before welding, wherein the surface of the fiber reinforced composite plate 3 is cleaned with a detergent and a soft cloth before welding to remove oil, dust and impurities.
[0035] like Figure 1 As shown in the figure, the metal sheet area on the side to be welded with the fiber reinforced composite sheet is defined as the area to be welded. In this area, two laser surface treatments are performed in sequence. The scanning path of the first treatment is as follows: Figure 2 As shown, the shaded area is the unetched area.
[0036] like Figure 2As shown: Figure a is the first scanning path diagram, Figure b is the second scanning path diagram, and Figure c is a schematic diagram of the structure obtained by etching. The thin solid line in the figure is the laser scanning path before the array, and the direction indicated by the arrow on the solid line is the laser scanning direction. This is used as an array unit, and the first scanning and the second scanning are performed in sequence in the array form to obtain the target microstructure 4 of the array, where the number of thin solid lines contained in the array unit is only for reference and needs to be determined according to actual conditions. Specific embodiments
[0037] In this example, the friction stir lap welding method is used. The test materials selected are 75mm×50mm×2mm 6061 aluminum alloy plate and 65mm×50mm×2mm carbon fiber reinforced PA66 plate (carbon fiber content is 30%). The aluminum alloy plate is on the top and the fiber reinforced composite plate is on the bottom. The target microstructure is processed in the to-be-welded area on the surface of the aluminum alloy plate by laser surface treatment before welding.
[0038] Welding is carried out according to the following steps: Step 1: Draw the laser scanning path. First, draw a closed line with the geometric parameters of a regular triangle with a side length of 520μm and a corner radius of 300μm. Then, based on this, process the inside and outside at an equal distance of 10μm to obtain the first scanning path.
[0039] Step 2: Copy and paste the first scan path, press Figure 2 As shown, redundant lines are removed to obtain the second scanning path.
[0040] Step 3: Set the laser processing parameters: center wavelength 1064nm; pulse width 9ns; laser frequency 600kHz; laser power 17.5W; scanning speed 25mm / s, scanning times 3 times, use sandpaper to polish the area to be welded of the aluminum alloy plate to remove the surface oxide film, then start the laser, and process the target microstructure 4 in the 10×60mm area to be welded on the surface of the aluminum alloy plate.
[0041] Step 4: Before welding, seal and store the laser-treated 6061 aluminum alloy sheet to avoid touching the surface treatment area. Before welding, use a detergent and soft cloth to thoroughly clean the plastic surface of the carbon fiber reinforced PA66 sheet to remove oil, dust and other impurities, and then prepare for welding.
[0042] Step 5: Place the weldments in the fixture in sequence, with the 6061 aluminum alloy sheet on the upper layer and the carbon fiber reinforced PA66 sheet on the lower layer. The overlap width is 12 mm. After clamping, fix the fixture on the workbench of the friction stir lap welding machine to prevent the weldments from moving after welding.
[0043] Step 6: Adjust the position relationship between the stirring head and the weldment, and set the welding parameters: stirring head speed 1200 r / min, welding speed 280mm / min, stirring head sinking depth 0.2mm. During the welding process, the welding parameters remain fixed. After welding, remove the weldment.
[0044] The above is only an embodiment of the present application and does not constitute any form of limitation to the present application. Although the present application is disclosed as above with a preferred embodiment, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A high-quality lap welding method for dissimilar materials based on laser surface treatment, It is characterized in that The following steps are involved: S1: laser surface treatment is performed on a metal sheet (1), a target microstructure (4) is etched in a welding area (3), and a Schiff base polymer is introduced, wherein the polymer contains a Schiff base -RC=N- and a carbonyl group -C=O; S2: Stir friction lap welding the treated metal sheet (1) and the untreated fiber reinforced composite sheet.
2. The high-quality lap welding method for dissimilar materials based on laser surface treatment according to claim 1, It is characterized in that In step S2, the metal plate (1) is made of a lightweight metal material, such as magnesium alloy, aluminum alloy or titanium alloy; the fiber-reinforced composite plate is a carbon fiber-reinforced thermoplastic resin plate; the thermoplastic resin may be PEEK, PA66 or PPS; the thickness of the metal plate (1) and the fiber-reinforced composite plate are both 1.5-3 mm.
3. The high-quality lap welding method for dissimilar materials based on laser surface treatment according to claim 1, It is characterized in that In the step S1, the central wavelength of the laser surface treatment of the metal plate (1) is 1064 nm; the pulse width of the laser surface treatment is 9-30 ns; the laser frequency of the laser surface treatment is 450-600 kHz; the laser power of the laser surface treatment is 15-25 W; the scanning speed of the laser surface treatment is 10-30 mm / s, and the number of scanning times is 3-5 times.
4. The high-quality lap welding method for dissimilar materials based on laser surface treatment according to claim 3, It is characterized in that In step S1, the metal plate (1) is subjected to laser surface treatment twice. The first laser surface treatment is performed on the area to be welded (3) to etch out the target microstructure (4), and then terephthalaldehyde C8H6O2 and aniline C6H5NH2 are introduced into the area to be welded (3). The second laser surface treatment heats the terephthalaldehyde C8H6O2 and aniline C6H5NH2 introduced into the area to be welded (3) to generate a Schiff base polymer, which then reacts and bonds with the metal ions of the metal plate (1).
5. The high-quality lap welding method for dissimilar materials based on laser surface treatment according to claim 4, It is characterized in that The cross section of the target microstructure (4) etched from the metal plate (1) is a triangle, the three sides of the triangle are provided with concave arcs, and the corners of the triangle are rounded; a groove is formed between the etched target microstructure (4) and the metal plate (1), the groove cross section is an inverted trapezoid, the groove width is 200-400 μm, the groove depth is 200-400 μm, and the groove aspect ratio is 1-2.
6. The high-quality lap welding method for dissimilar materials based on laser surface treatment according to claim 5, It is characterized in that In the step S1, the width of the area to be welded (3) is 10-12 mm.
7. The high-quality lap welding method for dissimilar materials based on laser surface treatment according to claim 1, It is characterized in that In step S2, the stirring head of the friction stir lap welding is perpendicular to the top of the area to be welded (3), and a lap method is adopted in which the metal plate (1) is on the top and the fiber reinforced composite plate is on the bottom, and the lap width is 12-15 mm.
8. The high-quality lap welding method for dissimilar materials based on laser surface treatment according to claim 7, It is characterized in that In the step S2, the stirring head rotation speed of the friction stir lap welding is 1000-1500 r / min, the welding speed of the friction stir lap welding is 150-300 mm / min, and the sinking depth of the stirring head of the friction stir lap welding is 0.2-0.4 mm.
9. The high-quality lap welding method for dissimilar materials based on laser surface treatment according to claim 7, It is characterized in that In the step S2, the metal sheet (1) after the laser surface treatment is sealed and stored before welding, and the surface of the fiber-reinforced composite sheet is cleaned with a cleaning agent and a soft cloth before welding to remove oil, dust and impurities.
Citation Information
Patent Citations
Method for treating connection strength of reinforced composite material and metal through ultrafast laser
CN113414496A
Method for ultrasonic enhanced connection of metal / chopped carbon fiber composite material
CN114571736A
Friction micro-riveting welding method for light alloy and fiber reinforced composite material
CN114643406A
Semiconductor device and method for manufacturing semiconductor device
CN115023816A
Laser welding strengthening method for metal and carbon fiber reinforced composite material
CN115091039A
Cited By
Dissimilar metal friction welding interface regulation and control layer and aluminum steel friction welding method
CN119703320A
Laser composite self-piercing riveting process for connecting aluminum alloy plates
CN120326125A
Continuous ultrasonic welding method for composite material based on interface microstructure
CN121246251A
